Rogelio Salmona : a espessura heterogênea de uma superfície uniforme - Ossani, Taís de Carvalho (2018)
This paper proposes a method of study and recognition about the work of the Colombian architect Rogelio Salmona, with the intention to contribute to new discussions about his work, in the range of academic research, historiography and project studies. The aim is to study deeply the plurality of strategies adopted by the architect through a fragment of four works - the Colombian Society of Architects (1962), the residential Towers of the Park (1964), the urban renovation New Santa Fe (1983) and the General Archive of the Nation (1988) - all located in Bogotá, Colômbia. The dissertation consists of two complementary parts. The first part: recognition and selection, includes chapters 1 and 2, which first presents the universe that covers bibliographies and academic research concerning the architect and his biography. In a second moment, about sixty projects of the architect are redesigned and categorized with the purpose of selecting the works sample that is adequate and helps in the search for the plurality of strategies adopted by the architect. In the second part: practical-reflexive exercise, composed of chapters 3 and 4, the critical and referenced studies of the four works are realized and some combinatorial and interpretative graphs, of the same works, are generated with the purpose of comprehend the diversity of the actions that constitute this snippet of architect's works. The paper ends with final considerations that relate the questions treated at the end of chapter 1 to the project investigations developed in chapters 3 and 4. To conclude, through the architect's practice, pertinent elements to investigate the plurality existing within the uniform surface postulated by the readings of the 1980s about the architect.